(3TQM OjhGf GeQF GdbjS Hg MLQ GdcfOis - (3CHi HcQ YGUe Hf CjhH GdHWdjhSjs; (3GeQD GdbjS , GeQD GdbjSs
(3ChdgG (B:s
(3HMeO Gddg fSJaJM hHGdUdg Ydi eMeO fSJfLM CYde CHbGc Gddg Cf ddTYQGA CZQGVkG JfRd YfgG GdYdeGA s
(3BNQgG (B:s
(3Efi MdaJ jejfkG ZjQ cGPHI Cfc Cbda EdG eGLfi GdbeQ ceG jdGJ HQCS Gdadcg GdhHQ Je TYQ GeQF GdbjS Hf MLQ hGdMeO ddg s
(3JSNI KGfjIs
(3fJab ai ChdgG hBNQgG eY GdfSNNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
Keywords: (3GdCOHs